Performance Indicators in Football: Examining the impact of Passing and Crossing Efficiency on Team Rankings - Mohamad Nizam Nazarudin; Ardo Okilanda; Rabiu Muazu Musa; Lao Xiaoyan (CV. FOUNDAE, 2025)
Background: Passing and crossing efficiency are recognized as key factors in football performance, yet their contextual influence in Southeast Asian competitions has been underexplored. The 2024 Mitsubishi Electric Cup offers a vital setting to examine how these technical indicators affect team tactics and rankings within the region's evolving football landscape.Aims: This study aims to analyze team distribution performance through accurate passes, pass success rates, and crossing accuracy, and to determine how these variables relate to team rankings and tactical strategies in both offensive and defensive phases.Methods: A quantitative approach was employed using descriptive statistics, Pearson correlation, and regression analysis. Data were collected from official tournament databases. The independent variables were accurate passes, pass success rate, and crossing accuracy, while team ranking served as the dependent variable.Results: Data from ten teams were analyzed. Thailand recorded the highest pass success rate (85%) and passing volume (3,373 passes), showing strong possession control. Vietnam achieved the highest crossing accuracy (60%), indicating effective wide-play. Correlation analysis revealed a moderate relationship between pass success rate and crossing accuracy (r = 0.65, p < 0.05). Regression results confirmed that pass success rate significantly predicted passing volume (R² = 0.45, p < 0.05).Conclusion: Teams with higher pass accuracy demonstrated superior control and competitive performance, while crossing efficiency was more context-dependent. Coaches and federations should emphasize structured passing drills and possession-based play, integrating crossing strategies selectively. Future studies should apply AI-assisted tactical modeling to enhance distribution and performance analysis in regional and global football